UPAYA MENINGKATKAN KEAKTIFAN BELAJAR EKONOMI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) - Eka Prasetyanta; Sunarto Sunarto; Leny Noviani (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aim of this research is to know the effort of implementation cooperative learning Student Teams Achievement Divisions (STAD) to improve economic learning activity at second grade students of SMA Negeri 1 Karanganom In Academic Year 2014/2015. The research model is Classrom Action Research. The researcher took the class of X.IIS.3 SMA Negeri 1 Karanganom in academic years of 2014/2015 as the subject for this research, whih consist of 26 students. The technique for collecting the data was: (a) observasion, (b) test, (c) interview, and (d) documentations. The procedure pf the research was: (a) planning, (b) planning, (c) observation, and (d) reflection. The research was conducted by two cycles, where each cycle carried out in three meeting, each meeting was conducted in 2x45 minutes. The conclusion of this study were: (1) learning activity has increased from 1st cycle to 2nd cycle. It can be revealed that Oral Activites has increased 11,54% from 73,07% initially to 84,61%, Listening Activities has increased 9,63% from 80,76 % initially to 90,38%, Writing Activities has increased 13,47% from 80,76% initially to 94,23%, Mental Activities has increased 17,28% from 69,23% initially to 84,61%, Emotional Activities has increased 19,31% from 78,84% initially to 96,15%. (2) from the result as learning score has increased 5,38% from 77,69% to 83,07% in 1st cycle to 2nd cycle.